Developmental Tendencies of a Success Story: Intersectionality's Past, Present, and Future (KULT_online, 2012)
The volume Framing Intersectionality: Debates on a Multi-Faceted Concept in Gender Studies (2011), published by Helma Lutz, Maria Teresa Herrera Vivar, and Linda Supik, provides an historical overview of the currently popular research paradigm of intersectionality. It traces the development of intersectionality from its establishment within US law studies up to present debates on masculinity, transculturality, and heteronormativity and introduces future research potential. Beginning with Kimberlé W. Crenshaw’s foundational text, the book assembles, in particular, articles from gender studies and social sciences which illustrate the achievements of intersectionality and highlight possible areas of conflict. Hence, the collection lives up to its title in offering a comprehensive framework of intersectional research able to serve as an initiation into the topic, and also as a platform for additional readings.